Six-membered ring systems: with O and/or S atoms - Santos, Clementina M.M. (2015)
In 2013, a large variety of publications dedicated to the synthesis 0- and S-6-membered heterocycles emerged, with special emphasis on the synthesis of natural oxygen derivatives. The importance of microwave irradiation in the synthesis of 0 - 6- membered compounds (14SC3047), the synthesis of several of their natural derivatives or key intermediates in a gram-scale fashion covering the literature from the twenty-first century (14NPR419), the isolation, synthesis and structural elucidation of the natural tetrahydropyran amphidinol 3 (14NPR468) and the chemistry of the secondary metabolite silybin , a 2-aryl-4H-chroman-4-one, were reviewed (14NPR1138).An overview of the natural occurrence, synthesis and biological properties of chromones (14CR4960), synthesis and structure-activity relationship of antileishmanial phenolic natural and synthetic flavonoids, isoflavones, coumarins and xanthones (14CR1 0369), the synthesis of natural products and natural-productlike compounds based on chroman-type structures (14SL1953) and the natural occurrence and synthesis of chromenes, coumarins and fused chromene-type cmnpounds as well as the application of dihydrobenzo[h] chromenes in the construction of various synthetic organic compounds (14CR 1 0476) have also been surveyed.